Moderate Inflation in Poland : A Real Story - Pujol, Thierry (IMF Working Papers; Working Paper ;, 1996)
Why is moving from moderate to low inflation almost always slow or costly? This paper answers this question, based on the Polish experience. First, reflecting the transition to a market economy, Polish inflation has been marked by significant changes in relative prices. Second, as wage and price indexation takes root, the inflationary effect of shocks to relative prices is magnified. Third, lagging structural reform, including the failure to extend hard budget constraints to all sectors of the economy, makes monetary policy less effective. Reduced money supply growth with structural reform offers the best prospect for moving to low inflation.